Design a hairpin bandpass filter for 5 GHz unlicensed WiMax band / Nor Hayati Malek - Malek, Nor Hayati (2009)
This paper presents a hairpin bandpass filter design for 5 GHz unlicensed WiMax band. The fdter is designed at 5.788 GHz centre frequency, with a bandwidth of 125 MHz bandwidth that is about 0.02% of its centre frequency, 0.1 dB ripples and consists of 3 elements. It is then simulated using Computer Simulation Technology (CST), then be fabricated on Roger 4350B that have a dielectric constant, e, of 3.48 and substrate thickness, h of 1324 mm. The fdter is then being measured using Vector Network Analyzer (VNA) and the measurement results show a good agreement with the simulation results.